1991
DOI: 10.1017/s0022215100117505
|View full text |Cite
|
Sign up to set email alerts
|

Exostosis of the external auditory canal: an interesting histopathological finding

Abstract: Perforation of the tympanic membrane is a frequent complication of surgery for exostoses of the external auditory canal. We report an unusual histopathological finding in a temporal bone containing external canal exostoses which suggests that some of these perforations may be unavoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
1
5
0
1
Order By: Relevance
“…Microscopic examination (Fig. 4) of the exostosis revealed that the structure exhibits several subperiosteal layers of dense compact bone in a circumscribed area, similar to previously reported histology of external auditory exostoses (Graham, 1979;Kemink and Graham, 1982;Pace-Balzan and Hawke, 1991).…”
supporting
confidence: 86%
“…Microscopic examination (Fig. 4) of the exostosis revealed that the structure exhibits several subperiosteal layers of dense compact bone in a circumscribed area, similar to previously reported histology of external auditory exostoses (Graham, 1979;Kemink and Graham, 1982;Pace-Balzan and Hawke, 1991).…”
supporting
confidence: 86%
“…When exostoses cause symptoms, usually recurrent otitis externa with otalgia, conductive hearing loss or tinnitus, they may require excision. The complications of surgical treatment include perforation of the tympanic membrane (which in some cases may be inevitable), 16 meatal stenosis, infection, residual tinnitus, hearing loss and facial nerve palsy. Surgery is usually successful in relieving the patients’ symptoms, although previous studies analysing their postoperative course fail to show any recurrence of exostoses after surgery, 17,18 which may be partly explained by diminished aquatic sports activity 19 .…”
mentioning
confidence: 99%
“…The remaining 30% arise from the floor of the meatus or its upper edge (Wang et al, 2005). Rarely, a tumor may descend from the roof of the outer ear canal and together with the anterior and posterior exostoses, they almost occlude the auditory meatus and produce a characteristic triangular constriction (Mays, 1998;Wong et al, 1999;Pace-Balzan and Hawke, 1991). From the microscopic point of view, external auditory exostoses are characterized by subperiostal and lamellar bony additions.…”
Section: Introductionmentioning
confidence: 99%
“…From the microscopic point of view, external auditory exostoses are characterized by subperiostal and lamellar bony additions. They involve a great number of osteocytes (Hutchinson et al, 1997) and are composed of dense compact bone (Pace-Balzan and Hawke, 1991;Aufderheide and Rodriguez-Martin, 1998).…”
Section: Introductionmentioning
confidence: 99%